2011
DOI: 10.1021/ic200368g
|View full text |Cite
|
Sign up to set email alerts
|

Polymer-Anchored Peroxo Compounds of Vanadium(V) and Molybdenum(VI): Synthesis, Stability, and Their Activities with Alkaline Phosphatase and Catalase

Abstract: We generated a series of new polymer-bound peroxo complexes of vanadium(V) and molybdenum(VI) of the type [VO(O(2))(2)(sulfonate)]-PSS [PSS = poly(sodium 4-styrene sulfonate)] (PV(3)), [V(2)O(2)(O(2))(4)(carboxylate)VO(O(2))(2)(sulfonate)]-PSSM [PSSM = poly(sodium styrene sulfonate-co-maleate)] (PV(4)), [Mo(2)O(2)(O(2))(4)(carboxylate)]-PA [PA = poly(sodium acrylate)] (PMo(1)), [MoO(O(2))(2)(carboxylate)]-PMA [PMA = poly(sodium methacrylate)] (PMo(2)), and [MoO(O(2))(2)(amide)]-PAm [PAm = poly(acrylamide)] (PM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
52
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 134 publications
9
52
2
Order By: Relevance
“…61,62 The results are also consistent with the proposed structures of the pMo containing macrocomplexes PMo 1 , PMo 2 and PMo 3 presented in figure 2a-c. 62 The metal loading on the compounds, estimated on the basis of Energy Dispersive X-ray (EDX), atomic absorption spectroscopy (AAS) and elemental analysis data was found to vary within the range 2.1 (PV 1 ) to 0.7 (PMo 3 ) mmol g −1 of polymer. 61,62 The scanning electron micrographs of the polymer anchored complexes (figure 3) revealed that the metal ions are distributed across the surface of the polymers. The 51 V NMR spectra of PV 1 and PV 4 are presented in figure 4.…”
Section: Synthesis and Characterizationsupporting
confidence: 89%
See 4 more Smart Citations
“…61,62 The results are also consistent with the proposed structures of the pMo containing macrocomplexes PMo 1 , PMo 2 and PMo 3 presented in figure 2a-c. 62 The metal loading on the compounds, estimated on the basis of Energy Dispersive X-ray (EDX), atomic absorption spectroscopy (AAS) and elemental analysis data was found to vary within the range 2.1 (PV 1 ) to 0.7 (PMo 3 ) mmol g −1 of polymer. 61,62 The scanning electron micrographs of the polymer anchored complexes (figure 3) revealed that the metal ions are distributed across the surface of the polymers. The 51 V NMR spectra of PV 1 and PV 4 are presented in figure 4.…”
Section: Synthesis and Characterizationsupporting
confidence: 89%
“…61,62 Most notable finding of our study was that the polymer anchored and neat peroxo compounds induced their inhibitory effects on ALP via distinct mechanisms. 62,63 Moreover, polymer bound pV 61 and pW complexes 65 efficiently mediated oxidative bromination of organic substrates under mild condition at near neutral pH, considered as essential requirement of a biomimetic model. It was observed that even a minor change in co-ordination environment around the peroxometal moieties in the polymeric complexes could alter their bioactivity as well as their catalytic activity tremendously.…”
Section: Introductionmentioning
confidence: 72%
See 3 more Smart Citations